Influence of saHnity and food deprivation on growth and RNA-DNA ratio in red drum Sciaenops ocellatus (Pisces: Sciaenidae) - Chung, Kyung S (1993)
Juvenile Red drum Sciaenops ocellatus held in 30 ppl natural seawater or fresh water were starved or fed ad libítum for su weeks, and sampled each week for growth and for determination of RNA, DNA, and protein contents of white and red muscles and liver. Specific growth Tate and condition factor were used lo compare changes in nucleic acid and protein concentrations in fish tissues. Salinity had liule effect on growth, while starvalÍon caused a significant reducuon in all growth parameters and in the RNA-DNA ratio after three weeks. The RNA-DNA ralÍos of red and white muscles of the fed fish were greater than those of the starved fish and also were related to specific growth Tate and fish condition factor. Nucleic acid concentralÍons in liver were highly variable. Since wrute muscle predorninates and is more easily sampled in red drum than red muscle, and because it has less variable RNA-DNA ratios than liver, it is the tissue recornmended for nucleic acid analysis of physiological condition and growth.